FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BBLR DI RUMAH SAKIT BAKTI TIMAH - Walizah, Zika; Kusumajaya, Hendra; Retnoningrum, Dyah (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2025)
Low Birth Weight (LBW), defined as a baby weighing less than 2,500 grams, is a determinant factor in most neonatal deaths. LBW is a public health problem, both short-term and long-term, and remains a major cause of perinatal morbidity and mortality. LBW usually occurs in preterm infants, also known as LBW. This study was conducted using a cross-sectional survey and the Chi-Square test, with univariate and bivariate analyses. Probability sampling was used. The population in this study was low birth weight infants. The sample size was 94 infants. Data analysis used the Chi-Square test with a 95% confidence interval. The results of this study revealed a significant association between maternal age (P-value = 0.000), parity (P-value = 0.009), and pregnancy spacing (P-value = 0.017) and the incidence of low birth weight. This study recommends that hospitals provide education or counseling on factors related to the incidence of low birth weight. Keywords: Maternal age, Parity, Pregnancy spacing.